2015
DOI: 10.1016/j.apgeog.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to spatial inequality in academic achievement in Ghana: Analysis of district-level factors using geographically weighted regression

Abstract: a b s t r a c tLike most Sub-Saharan African countries, Ghana's basic educational system continues to undergo reform, receiving substantial investment to ensure all citizens have access to quality educational opportunities regardless of where they live. Although the reforms have markedly improved access to education at the junior high school level, the overall level of academic achievement among Ghana's population remains low, especially in deprived areas of the country. The low rate of achievement warrants ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 15 publications
1
27
1
1
Order By: Relevance
“…Within the dominant quantitative methods, scholars such as Akyeampong (2006, 2009), Ansong et al (2015a), Lewin and Sabates (2011), Nishimura (2008), Spaull and Taylor (2012, 2014) have employed cross‐sectional designs to observe patterns and characteristics of basic education access and outcomes among various groups of children in Ghana and SSA. Others, for example, Ansong et al (2015b), Lewin (2009), and Maliti (2018) have used longitudinal methods to trace and observe levels of inequality and educational outcomes among various groups of children. Beyond these studies, international, bilateral, and multilateral organisations like the World Bank, UNICEF, UNESCO, and USAID produce volumes of empirical studies and reports on educational access in SSA that rely on analysis of existing indicator‐based datasets to produce macro‐level results (Burns et al , 2003; Birger and Craissati, 2009; UNESCO, 2015).…”
Section: What Is the Evidence Base Of Research In Ube In Ghana And Ssa?mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the dominant quantitative methods, scholars such as Akyeampong (2006, 2009), Ansong et al (2015a), Lewin and Sabates (2011), Nishimura (2008), Spaull and Taylor (2012, 2014) have employed cross‐sectional designs to observe patterns and characteristics of basic education access and outcomes among various groups of children in Ghana and SSA. Others, for example, Ansong et al (2015b), Lewin (2009), and Maliti (2018) have used longitudinal methods to trace and observe levels of inequality and educational outcomes among various groups of children. Beyond these studies, international, bilateral, and multilateral organisations like the World Bank, UNICEF, UNESCO, and USAID produce volumes of empirical studies and reports on educational access in SSA that rely on analysis of existing indicator‐based datasets to produce macro‐level results (Burns et al , 2003; Birger and Craissati, 2009; UNESCO, 2015).…”
Section: What Is the Evidence Base Of Research In Ube In Ghana And Ssa?mentioning
confidence: 99%
“…The above results show that the current global practice of defining UBE, largely through enrolment statistics, remains an insufficient indicator for determining progress or success in the field of basic education, especially in the SSA context. Unlike many developed regions where children largely have access to equal opportunities and resources to complete basic education, the basic education process in Ghana and SSA is experienced differentially depending on factors such as location, socio‐economic status, and to some extent gender (Dabalen et al , 2015; Ansong et al , 2015b). The need to widen the ‘brackets’ of access and redefine how it is operationalised therefore remains a prudent goal in the search for equity and justice in basic education access for all children in the SSA region.…”
Section: What Is the Evidence Base Of Research In Ube In Ghana And Ssa?mentioning
confidence: 99%
“…GWR is becoming a more commonly used technique in spatial analysis. For example, it has been applied to investigate commuting patterns (Lloyd and Shuttleworth, 2005), spatial distribution and determinant of bank branches (Ansong et al, 2015b), voters apathy in presidential election (Taiwo and Ahmed, 2015), spatial inequality in academic achievement (Ansong et al, 2015a), and spatial patterns of fire density (Oliveira et al, 2014). These studies demonstrated that spatial phenomenon can be better analysed by accounting for the spatial effects (local dependence and spatial heterogeneity) using GWR (Li et al, 2009).…”
Section: Data Sources and Variablesmentioning
confidence: 99%
“…The continued reliance on educational attainment data to estimate adult literacy rates is surprising, especially in light of mounting evidence from school-based studies in Asia and Africa that many students in advanced grades lack academic proficiency ( Zhang 2006 ). In fact, there is growing interest in identifying the causes and consequences of students' underachievement ( Ahmed and Arends-Kuenning 2006 ; Ansong et al 2015 ; Dembélé and Lefoka 2007 ; Fehrler, Michaelowa, and Wechtler 2009 ; Glick and Sahn 2000 ; Kasirye 2009 ). Yet, despite recognition that many students do not acquire academic skills, the assumption prevails that adults who went to primary school - in some instances many decades ago - learned how to read and have maintained the skill through adulthood.…”
Section: Introductionmentioning
confidence: 99%